Fish Diversity And Population At Selected Feeder Rivers To Bukit Merah Reservoir, Perak - Mohammad, Mohd Syaiful (2019)
A study of fish diversity and in-situ water parameter was carried out in five selected river feeders with eight sampling stations in Bukit Merah Reservoir (BMR) from November 2012 until Jan 2014 for 14 month of time period. The study area covers the upper and lower reaches of river feeders to Bukit Merah Reservoir. The overall water quality in five selected river feeders of Bukit Merah Reservoir can be classified under Class II (selected water parameters). A total of 1946 individuals of fish were caught using cast net with 42 species belonging to 16 families recorded in this study. Cyprinidae are the most dominant fish species recorded in this study with the composition of 38.1% followed by Bagridae (11.9%) and Channidae (9.5%).